2021
DOI: 10.1038/s41436-021-01287-7
|View full text |Cite
|
Sign up to set email alerts
|

Safe and persistent growth-promoting effects of vosoritide in children with achondroplasia: 2-year results from an open-label, phase 3 extension study

Abstract: Purpose Achondroplasia is caused by pathogenic variants in the fibroblast growth factor receptor 3 gene that lead to impaired endochondral ossification. Vosoritide, an analog of C-type natriuretic peptide, stimulates endochondral bone growth and is in development for the treatment of achondroplasia. This phase 3 extension study was conducted to document the efficacy and safety of continuous, daily vosoritide treatment in children with achondroplasia, and the two-year results are reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…Vosoritide binds to CNP receptors, which reduces FGFR3 activity and thereby stimulates bone growth. Subcutaneous administration of vosoritide improves growth in children 5 years of age and older with open epiphyses (Savarirayan et al 2020 , 2021 ). The most common AEs of vosoritide include injection site reactions, arthralgia, vomiting, and hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…Vosoritide binds to CNP receptors, which reduces FGFR3 activity and thereby stimulates bone growth. Subcutaneous administration of vosoritide improves growth in children 5 years of age and older with open epiphyses (Savarirayan et al 2020 , 2021 ). The most common AEs of vosoritide include injection site reactions, arthralgia, vomiting, and hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…Recently published follow-up data from the vosoritide phase 2 and phase 3 extension studies showed persistent improvements in annualized growth velocity in treated children with achondroplasia across age categories up to 60 months of treatment [ 11 , 12 ]. Overall, the panelists of the modified Delphi study expect that growth velocity increases with vosoritide will continue beyond 60 months, until final height is reached in individuals starting treatment before puberty and that those starting treatment earlier will more likely achieve a greater final height (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the pivotal phase 3 clinical trial showed increases in annualized growth velocity and height Z-scores after 52 weeks of treatment with vosoritide versus placebo and good tolerability [ 10 ]. Two-year follow-up data showed sustained increases in annualized growth velocity, continued improvements in height Z-score, and improvements in upper-to-lower body segment ratio versus untreated patients, without adverse effects on bone maturation [ 11 ]. Sixty-month data from a phase 2 study (N = 35) and its extension (N = 19) reported consistent findings [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adults with achondroplasia can experience lower quality of life (QOL) than do their counterparts without this condition 13,[20][21][22][23][24][25] . QOL is in uenced by a number of factors including disease severity, height, pain, age, self-esteem, social support, and perceived stigmatization 13,19,20 .…”
mentioning
confidence: 99%
“…These procedures involve multiple surgeries and prolonged recovery 11,24 . As an understanding of the pathogenesis of achondroplasia improves, attention is turning to pharmacologic treatments 6,25,26 . While the potential bene t of pharmacologic treatment is documented in the clinical literature, little is understood about how patients and families view the use of medications to improve endochondral bone growth in order to increase stature and, potentially, to ameliorate complications.…”
mentioning
confidence: 99%